Magnesium ion serum profile in chronic migraine: comparative study between treated and non-treated patients - Jesus, Alan Chester Feitosa de; Silva, Giselle Melo Fontes; Paixão, Marcelo Oliveira Ribeiro; Barreto, Felipe José Nascimento; Dantas, Luana Karla Braz Fonseca; Macedo, Philippe Joaquim Oliveira Menezes; Santos, Paulo Sérgio Faro; Santos, Larissy Lima; Nunes, Marco Antônio Prado (Headache Medicine, 2012)
Chronic migraine is recognized as a migraine complication and is characterized by frequency of attacks up to 15 days/ month for more than three months, in absence of painkiller abusive usage. Studies indicate that magnesium ion plays a role in migraine pathophysiology but, until now, they have never included only patients with chronic migraine as their population. Objective: To compare serum magnesium levels etween treated and non-treated chronic migraineurs. Methods: Twenty-two patients with chronic migraine were selected and divided in two groups (treated and non-treated), matched by sex and age, and submitted to serum dosage of magnesium ion for latter comparison. Result: The non-treated chronic migraineurs presented serum magnesium ion level within normal limits, but lower than those found in the treated group with a statistically significant difference. Conclusion: Similarly to other studies in the literature, this study stresses the importance of magnesium ion in the migraine pathophysiology, but studying only the chronic migraine patients.